Odpowiedź :
Cześć!
[tex]a = \sqrt{3\sqrt{5}-3}\\\\b = \sqrt{3\sqrt{5}+3}[/tex]
[tex]\sqrt{n} \cdot \sqrt{m} = \sqrt{n \cdot m} \ \Rightarrow \ \sqrt{3\sqrt{5}-3} \cdot \sqrt{3\sqrt{5}+3} = \sqrt{(3\sqrt{5}-3)(3\sqrt{5}+3)}[/tex]
Używamy wzoru skróconego mnożenia, zwanego różnicą kwadratów:
[tex]x^2-y^2 = (x-y)(x+y)[/tex]
Niech dla tych oznaczeń:
[tex]x=(3\sqrt{5}-3)\\y=(3\sqrt{5}+3)[/tex]
Wówczas:
[tex]\sqrt{(3\sqrt{5}-3)(3\sqrt{5}+3)} = \sqrt{(3\sqrt{5})^2 - 3^2} = \sqrt{9\cdot 5 -9} = \sqrt{45-9} = \sqrt{36} = 6[/tex]
Odpowiedź C.
Pozdrawiam!
[tex]a = \sqrt{3\sqrt{5}-3}}\\\\b = \sqrt{3\sqrt{5}+3}}\\\\ab = \sqrt{3\sqrt{5}-3}}\cdot\sqrt{3\sqrt{5}+3}} = \sqrt{(3\sqrt{5}-3)(3\sqrt{5}+3)} = \sqrt{45-9} = \sqrt{36} = 6\\\\6 \in (5,8)\\\\Odp. \ C.[/tex]